2010
DOI: 10.1007/s10571-010-9566-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Ca2+ Currents of Chromaffin Cells from Normotensive Wistar Kyoto and Spontaneously Hypertensive Rats

Abstract: Spontaneously hypertensive rats (SHR) are widely used as model to investigate the pathophysiological mechanisms of essential hypertension. Catecholamine plasma levels are elevated in SHR, suggesting alterations of the sympathoadrenal axis. The residual hypertension in sympathectomized SHR is reduced after demedullation, suggesting a dysfunction of the adrenal medulla. Intact adrenal glands exposed to acetylcholine or high K+ release more catecholamine in SHR than in normotensive Wistar Kyoto (WKY) rats, and ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…In previous papers, we characterized the Ca 2+ ‐currents expressed in acute adrenal slices (Segura‐Chama et al . , ; Hernández et al . ), Now, we identify the Ca 2+ ‐channel subtypes that control the activation of Ca 2+ ‐activated K + ‐channels after Ca 2+ ‐influx.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous papers, we characterized the Ca 2+ ‐currents expressed in acute adrenal slices (Segura‐Chama et al . , ; Hernández et al . ), Now, we identify the Ca 2+ ‐channel subtypes that control the activation of Ca 2+ ‐activated K + ‐channels after Ca 2+ ‐influx.…”
Section: Discussionmentioning
confidence: 99%
“…Second, when Na + ‐current was blocked, Ca 2+ ‐channels participated alone in generating APs of less amplitude; however, these reduced spontaneous APs cease after several seconds, presumably by inactivation of Ca 2+ ‐channels. Despite our report that no T‐type channels are detected in adult CCs of both mouse and SHR/WKY rats (Segura‐Chama et al ., ;2011; Hernández et al ., ), it has been shown that in cultured RCCs under sustained adrenergic stimulation, low‐voltage‐activated Ca 2+ channels are expressed and, following a lowered threshold of AP firing, may increase cell excitability during sustained sympathetic stimulation (Novara et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…Our laboratory recently compared the electrophysiological properties of voltage-gated Ca 2ϩ currents (I Ca ) in adrenal chromaffin cells (CCs) from WKY rats and SHR to determine whether the catecholamine hypersecretion reported in CCs from the SHR strain (27,28) was due to an augmented function of voltage-gated Ca 2ϩ channels. Our results showed that the electrophysiological and pharmacological properties of I Ca in adrenal CCs from SHR and WKY are indistinguishable (39), implying that catecholamine hypersecretion in SHR CCs cannot be attributed to augmented Ca 2ϩ entry, and also that the choice of the WKY strain as control was appropriate in this case. Nonetheless, we noticed differences in the kinetics and voltage dependence of I Ca recorded from CCs of the WKY/SHR strains compared with those recorded under the same conditions from adrenal CCs of other normotensive strains, e.g., Wistar rat and Balb-C mice (11,12,35), and we wondered if these differences in kinetics and voltage dependence could be of physiological significance.…”
mentioning
confidence: 73%
“…In the remaining sections, we focus on the electrophysiological properties of I Ca in WKY and SHR CCs. Our laboratory has previously shown that activation and inactivation kinetics, current density, voltage dependence of activation and inactivation, involvement of L-type Ca 2ϩ channels in the total I Ca , and autocrine modulation of I Ca in CCs from WKY and SHR rats are virtually indistinguishable (39).…”
Section: Methodsmentioning
confidence: 99%
“…Upon cessation of voluntary swimming movements (but before breathing had stopped), the trout were removed from anesthetic, weighed, and transferred to a surgical table where the gills were irrigated continuously with the same anesthetic solution for the duration of the surgery. To permit the measurement of dorsal aortic blood pressure (P DA) and blood sampling, and to permit injections of drugs (in the event of venous cannula failure), an indwelling polyethylene cannula (PE-50; Clay-Adams) was implanted into the dorsal aorta via percutaneous puncture (61). The cannula was flushed with chilled heparinized (50 U/ml ammonium heparin) Cortland saline (69) and sealed with a needle.…”
Section: Surgical and Experimental Proceduresmentioning
confidence: 99%